Instantaneous BeiDou–GPS attitude determination: A performance analysis - Nadarajah, Nandakumaran; Teunissen, Peter; Raziq, N. (Elsevier Ltd, 2014)
The advent of modernized and new global navigation satellite systems (GNSS) has enhanced the availability of satellite based positioning, navigation, and timing (PNT) solutions. Specifically, it increases redundancy and yields operational back-up or independence in case of failure or unavailability of one system. Among existing GNSS, the Chinese BeiDou system (BDS) is being developed and will consist of geostationary (GEO) satellites, inclined geosynchronous orbit (IGSO) satellites, and medium-Earth-orbit (MEO) satellites. In this contribution, a BeiDou–GPS robustness analysis is carried out for instantaneous, unaided attitude determination. Precise attitude determination using multiple GNSS antennas mounted on a platform relies on the successful resolution of the integer carrier phase ambiguities. The constrained Least-squares AMBiguity Decorrelation Adjustment (C-LAMBDA) method has been developed for the quadratically constrained GNSS compass model that incorporates the known baseline length. In this contribution the method is used to analyse the attitude determination performance when using the GPS and BeiDou systems. The attitude determination performance is evaluated using GPS/BeiDou data sets from a real data campaign in Australia spanning several days. The study includes the performance analyses of both stand-alone and mixed constellation (GPS/BeiDou) attitude estimation under various satellite deprived environments. We demonstrate and quantify the improved availability and accuracy of attitude determination using the combined constellation.